2017
DOI: 10.1159/000464469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Dermoscopic Features of the Scalp in 31 Patients with Dermatomyositis

Abstract: Background: Scalp involvement is not directly evaluated in patients with dermatomyositis (DM). Therefore, the exact frequency of scalp dermatomyositis (SDM) and its clinical and trichoscopic characteristics have been poorly described. Objective: The aim of this study was to determine the frequency and clinical and dermoscopic features of SDM in patients diagnosed with DM. Methods: We performed a descriptive prospective, cross-sectional observational study that included all patients diagnosed with DM at a Mexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 15 publications
2
45
0
Order By: Relevance
“…35 Recent studies have reported these findings in systemic autoimmune conditions, described as enlarged and tortuous in dermatomyositis and polymorphic, spider and arborizing with capillary loops in systemic sclerosis. 8,9 From our results, arborizing blood vessels were mostly located interfollicularly and are only alarming if prominent or thick, showing significantly higher odds of having SLE, while thin and sparse arborizing vessel was a frequent finding in normal controls. Scalp is a well-vascularized structure, the mechanism by which SLE causes increase in vessel number and dilatation is largely unknown but may be linked to angiogenesis induced by raised circulating serum angiogenic cytokines.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…35 Recent studies have reported these findings in systemic autoimmune conditions, described as enlarged and tortuous in dermatomyositis and polymorphic, spider and arborizing with capillary loops in systemic sclerosis. 8,9 From our results, arborizing blood vessels were mostly located interfollicularly and are only alarming if prominent or thick, showing significantly higher odds of having SLE, while thin and sparse arborizing vessel was a frequent finding in normal controls. Scalp is a well-vascularized structure, the mechanism by which SLE causes increase in vessel number and dilatation is largely unknown but may be linked to angiogenesis induced by raised circulating serum angiogenic cytokines.…”
Section: Discussionmentioning
confidence: 61%
“…In seborrheic dermatitis, the vessels increase in number but are normal‐looking whereas in psoriasis, twisted red loops are classically seen . Recent studies have reported these findings in systemic autoimmune conditions, described as enlarged and tortuous in dermatomyositis and polymorphic, spider and arborizing with capillary loops in systemic sclerosis . From our results, arborizing blood vessels were mostly located interfollicularly and are only alarming if prominent or thick, showing significantly higher odds of having SLE, while thin and sparse arborizing vessel was a frequent finding in normal controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically it is characterized by atrophic, erythematous, and scaly plaques, frequently accompanied by diffuse nonscarring alopecia [2]. Major trichoscopic features in scalp DM are enlarged capillaries and peripilar casts, both present in our patient [6]. In addition, trichoscop ic evaluation showed characteristic figures of “comma hairs,” “zigzag hairs,” and “pigtail hairs,” which suggested concomitant TC [3, 4].…”
Section: Discussionmentioning
confidence: 88%